Sectional matrix system in reconstruction of proximal contact in class ii resin restoration - Norun Nahar; AKM Bashar; Md Abdul Gafur; Didarul Haque Jeorge (Update Dental College, 2021)
Background: Clinicians always faces some challenges to reconstruct proper proximal contact while restoring class-II cavity with composite resin due to its viscosity, elastic property and polymerization shrinkage. It has been claimed that use of sectional pre-contoured matrix band with separation ring will produce more reliable result for reconstruction of optimal proximal contact in class II composite resin restoration. Purpose: To evaluate the efficacy of sectional pre-contoured matrix band with separation ring for reconstruction of optimal proximal contact in class II resin composite restoration. Methodology:  One Nissin manikin model having the facility of placing and screwing all upper and lower sets of artificial human teeth and sixty-two (62) artificial human mandibular permanent 1st molar teeth were collected. These 62 artificial human mandibular permanent 1st molars were randomly assigned in two groups (A & B) having 31 teeth in each. Standardized class II MO (mesio-occlusal) cavity were prepared on total 31 artificial 1st molar in group A. The 2nd premolar in the manikin model was replaced by metal cast duplicate and permanently fixed into the socket. All the Thirty-one (31) 1st molar teeth in group A, having Prepared class II cavity in each, were replaced one by another in the manikin distal to cast duplicated 2nd premolar and restored with composite resin by using sectional pre-contoured matrix band with separation ring and another 31 uninstrumented intact artificial 1st molars were include in group B as a reference group. After completion of restoration, newly developed proximal contact points were measured by using universal testing machine one after another. Same were also done in intact reference Group B. Measurement was done to assess the position of contact point, contact tightness and contact area of Group A and Group B on the same typodont. The results were analyzed statistically with post hoc Bonferroni test (P<0.05). Result: Teeth restored with sectional pre-contoured matrix with separation ring (group A) provided the tighter contact and broadened area of contact where all the contact points were placed  more occlusally compared to that of the intact un-instrumented reference teeth (group B).Statistically significant differences (P<0.05) were produced in all the three parameters with each other. Conclusion: Teeth restored with sectional pre-contoured matrix band with separation ring failed to reconstruct the optimal proximal contact in class-II composite resin restoration in comparison to intact uninstrumented reference tooth. Update Dent. Coll. j: 2021; 11(2): 16-19